Author Correction: Tuning the hierarchical pore structure of graphene oxide through dual thermal activation for high-performance supercapacitor - Jeongpil Kim (Nature Portfolio, 2021)
An amendment to this paper has been published and can be accessed via a link at the top of the paper.